Pengaruh Media Musik Populer Terhadap Keterampilan Menulis Puisi Siswa Kelas X SMA Swasta Amir Hamzah Medan Tahun Ajaran 2022/2023 - Dea Yohana Sidauruk (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to determine the effect of music illustration media on the poetry writing skills of Class X Students of Amir Hamzah Private High School Medan, Academic Year 2022/2023. The population in this study were all class X students of Amir Hamzah Private High School, while the sample used was 26 students who were determined using a random sampling technique. The method used in this study is the experimental quantitative method. The instruments used in this study consisted of observations and writing tests of explanatory texts which were assessed based on Diction, Imagination, Concrete Words, Themes and Messages. The average score obtained by students before using popular music media was 55 while the average score obtained by students after using the media popular music 67.69 So, it can be concluded that the test score after applying popular music media is higher than before. The results of data analysis in testing the hypothesis showed that tcount = 6.14 then consulted the t table, a significance level of 5%, and df = N – 1 = 26 – 1 = 25, obtained ttable = 1.69. Because the obtained tcount is greater than ttable, namely 6.14 > 1.70, the null hypothesis (Ho) is rejected and the alternative hypothesis H1 is accepted.